NATIONAL STRUGGLE AS ONE OF THE TYPES OF PHYSICAL CULTURE (American Journal of Pedagogical and Educational Research, 2023)
The article provides an overview of the Uzbek national wrestling Quresh: the history of the development of kurash, as well as the rules for evaluating Kurash competitions.